Program Theory and Theory of Change In Development Evaluation: A theoretical-practical review - Alvarez-Rojas, José Luis (2018)
Unlike other analytical or research exercises, Evaluation –understood as a professional practice– has clear applications and practical uses, which gives it a distinctive feature. Its main functions are the learning of experiences, feedback or improvement, and accountability to financial sources and public opinion involved in development programs. In this sense, the notions of Program Theory and Theory of Change have taken force and have consolidated into this new discipline. Nonetheless, full comprehension of the discipline may present difficulties, particularly for those starting in the field of evaluation, due not only to the myriad theoretical contributions and methodological efforts to apply these concepts, but also to a marked conceptual polysemy. This article reviews the main ideas and arguments related to these two notions and suggests that both concepts are synonymous and serve the interests of evaluation, which makes it a fundamental element in the practical exercise.